ESTETIKA lDEATIONAL FOTO PREWEDDING STYLE BALI - Cokorda Istri Puspawati Nindhia; Setiawan, I Nyoman Anom Fajaraditya (Jurnal Bahasa Rupa, 2019)
The combination of technology and art makes photography a complex work of art and a media of images that also gives meaning and message. The work of photography comes from certain creative concepts rooted in basic ideas, which then appear in a photoshoot. Bali prewedding style photo as a form of photographer's creativity, because in the process requires high creativity. The process of photography combining ideas and objects of photographs and photographers can be intertwined perfectly to produce the best photos. This study uses qualitative methods, supported by several theories to dissect the purpose of research, namely the theory of forms to dissect aspects of Balinese style prewedding photo forms, aesthetic theories to dissect aesthetic concepts, function theory to dissect function aspects, and semiotic theory to dissect meaning in photographs Balinese style prewedding. The results obtained, namely, the form of ideas in making prewedding photos based on ideas is a form of photo prewedding with Balinese architecture background. The Balinese style prewedding photo process is based on the social life of the people and the form of Balinese style prewedding based on Balinese style fashion.